2021
DOI: 10.1515/biol-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of fatty acids in Tripterygium wilfordii multiglucoside- and triptolide-induced liver-injured rats

Abstract: Tripterygium wilfordii multiglucoside (TWM) is a fat-soluble extract from a Chinese herb T. wilfordii, that’s used in treating rheumatoid arthritis, nephrotic syndrome and other skin diseases. Triptolide (TP) is a major active component in TWM. However, clinical applications of TWM are limited by its various toxicities especially hepatotoxicity. In recent studies, it has been reported that drug-induced liver injury (DILI) could induce the disorder of lipid metabolism in animals. Hence, this study focuses on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In vertebrates, the liver is the major organ for FA production and metabolism. It is predictable that any damage to the liver will cause a change in the balance of FA levels, including free and esterified FAs [ 54 ]. A high quantity of free fatty acids in the body can cause a considerable amount of lipids to accumulate in hepatic cells, causing cell membrane, mitochondria and lysosome damage [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, the liver is the major organ for FA production and metabolism. It is predictable that any damage to the liver will cause a change in the balance of FA levels, including free and esterified FAs [ 54 ]. A high quantity of free fatty acids in the body can cause a considerable amount of lipids to accumulate in hepatic cells, causing cell membrane, mitochondria and lysosome damage [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous gavage of TP resulted in significant upregulation of the liver X receptor-alpha (LXR)/sterol regulatory element binding transcription factor 1 (SREBP-1) signaling axis in females, while male rats showed only slight changes, resulting in more lipid droplets in TP-treated female rats than in TP-treated male rats, which might be a factor in the sex differences in TP-induced hepatotoxicity ( Jiang et al, 2016 ). In addition, targeted fatty acids analysis showed that TP exposure induced significant changes in fatty acid levels in the livers of rats and mice ( Li et al, 2017 ; Liu et al, 2021 ).…”
Section: The Mechanisms Of Tp-induced Hepatotoxicitymentioning
confidence: 99%
“…Based on different data sources, including the NMPA ( CFDA., 2014 ), the Liver Tox website ( Hoofnagle et al, 2013 ), case series reports, case reports, animal experiments, and in vitro experiments, etc., we reviewed common herbs related to HILI to provide a reference and basis for clinical and experimental reserach. Commonly herbs associated with HILI include PM ( Tu et al, 2015 ; Wang et al, 2016 ; Zhang B. et al, 2017a ; Tu et al, 2019a ; Tu et al, 2019b ; Li et al, 2019 ; Zhang et al, 2019 ), PF( Wu et al, 2017 ; Wang et al, 2018b ; Qin et al, 2021 ), Epimedii Folium (EF) ( Zhang et al, 2018 ; Gao et al, 2020 ; Wang et al, 2020 ; Gao Y. et al, 2021a ), Dictamni Cortex (DC) ( Huang et al, 2017 ; Shi et al, 2019 ; Shi, 2020 ), Gynura Segetum (GS) ( Gou et al, 2017 ; Ding and Xiong, 2018 ; Li et al, 2018 ; Tong et al, 2021 ), Rhizoma Dioscoreae Bulbiferae (RDB) ( Wang and Liao, 2018a ; Li C. Y. et al, 2020a ; Hou et al, 2020 ; Chen D. Y. et al, 2021a ), Senecionis Scandentis Hebra (SSH) ( Xiong et al, 2020 ; Jiang et al, 2021 ; Ye et al, 2021 ), Tripterygii Radix (TR) ( Yao et al, 2016 ; Zhu C. S. et al, 2018a ; Zhou et al, 2018 ; Zhou et al, 2018 ; Song et al, 2019 ; Liu et al, 2021 ), Bruceae Fructus (BF) ( Ma and Chen, 2014 ; Wu et al, 2018 ), Rhei Radix Et Rhizoma (RRR) ( Wang et al, 2011 ; Yao et al, 2020 ; Huo et al, 2021 ). The NMPA has warned of a risk of liver injury in TCM preparations including Yangxue Shengfa capsules ( CFDA., 2014 ), Shouwu tablet ( CFDA., 2014 ), Shouwu pill ( CFDA., 2014 ), Shouwu Yanshou tablet ( CFDA., 2014 ), Shouwu Yanshou granules ( CFDA., 2014 ), Xianling Gubao capsule ( Li J. et al, 2020b ), Zhuanggu Guanjie pill ( ...…”
Section: Pharmacoepidemiologymentioning
confidence: 99%